(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The poets of Al-Andalus derived the ridicule of the Islamic dogmas from the political conditions that spread in Al-Andalus, and these conditions have inflicted injustice and persecution on the people of Al-Andalus, and from this point of view, the poets of AlAndalus turned to criticize the jurists and clerics who support power and strengthen their authority through their religious influence. Through this, some poets have rebelled against the teachings of religion, and have gone beyond the boundaries of taste, morality, Customs and social traditions 0 religious cynicism in Andalusian poetry is represented by rebellion against religious values, underestimation of the sacred and intolerance of a religious doctrine intolerance based on underestimation and ridicule of other religious doctrines 0 and cynicism, which is a manifestation of social manifestations, is manifested in and queer 0